Penguatan Empati dan Pemahaman Teman Sebaya terhadap ABK melalui Psikoedukasi Kelompok di Kelas Inklusi SMK - Widyastuti Widyastuti; Rosna Nur Faizah; Evania Surya Dewi (Universitas Muhammadiyah Mataram, 2026)
Abstract: Regular students in inclusive classrooms often exhibit inflexible responses toward peers with disabilities, particularly those with Autism Spectrum Disorder (ASD) and slow learner characteristics, primarily due to a lack of knowledge rather than ill intent. This community service activity aimed to strengthen peer roles in inclusive classes at SMKN 1 Sidoarjo through group psychoeducation, involving 66 students from classes X-TKR 1, X-TKR 2, and XII-TAV as part of an MBKM internship program. The activity employed a pretest-posttest design using the Interpersonal Reactivity Index (IRI) to measure empathy in 48 students who completed both measurements (X-TKR 1 and X-TKR 2), and a Likert scale (1–5) to assess understanding and perception of disability knowledge across all 76 participants. Results showed a significant increase in empathy scores (N = 48; M pretest = 76.50; M posttest = 80.21; p < .001; d = 0.860, large effect), substantial improvement in understanding of ABK characteristics across all three classes (average increase = 1.41 points; p < .001; d = 1.718), and increased perception of the importance of disability knowledge (average increase = 0.86 points; p < .001; d = 0.945). Students also demonstrated the ability to formulate concrete supportive actions for peers with ASD and slow learner. These findings confirm that group psychoeducation is an effective intervention for enhancing empathy, knowledge, and prosocial behavior among regular students in inclusive settings. Abstrak: Siswa reguler di kelas inklusi kerap menunjukkan respons yang kurang fleksibel terhadap teman penyandang disabilitas, khususnya mereka yang tergolong Autism Spectrum Disorder (ASD) maupun slow learner, yang umumnya bersumber dari ketidaktahuan bukan dari niat buruk. Kegiatan pengabdian masyarakat ini bertujuan menguatkan peran teman sebaya di kelas inklusi SMKN 1 Sidoarjo melalui psikoedukasi kelompok, melibatkan 66 siswa dari kelas X-TKR 1, X-TKR 2, dan XII-TAV dalam kerangka program magang MBKM. Kegiatan menggunakan rancangan pretest-posttest dengan Interpersonal Reactivity Index (IRI) sebagai alat ukur empati pada 48 siswa yang mengikuti pengukuran secara lengkap (X-TKR 1 dan X-TKR 2), serta skala Likert 1–5 untuk mengukur pemahaman dan persepsi pentingnya pengetahuan ABK pada seluruh 76 peserta. Hasil menunjukkan peningkatan signifikan skor empati (N = 48; M pretest = 76,50; M posttest = 80,21; p < 0,001; d = 0,860, efek besar), peningkatan substansial pemahaman tentang karakteristik ABK di ketiga kelas (rata-rata selisih = 1,41 poin; p < 0,001; d = 1,718), dan peningkatan persepsi pentingnya pengetahuan ABK (rata-rata selisih = 0,86 poin; p < 0,001; d = 0,945). Siswa juga mampu merumuskan bentuk bantuan konkret bagi teman dengan ASD maupun slow learner. Temuan ini mengonfirmasi bahwa psikoedukasi berbasis kelompok merupakan intervensi yang efektif untuk meningkatkan empati, pemahaman, dan perilaku prososial siswa reguler di lingkungan inklusi.